• 2022-06-28
    若给定条件表达式(x)? (a++):(a--), 则表达式x ( )。
    A: 和(x==0)等价
    B: 和(x==1)等价
    C: 和(x!=0)等价
    D: 和(x!=1)等价
  • C

    内容

    • 0

      ‍若给定条件表达式(m)?(a++):(a--),则其中表达式m()。‎ A: 和(m==0)等价 B: 和(m!=0)等价 C: 和(m==1)等价 D: 和(m!=1)等价

    • 1

      ‌若给定条件表达式(m)?(a++):(a--),则其中表达式m()。‎ A: 和(m==0)等价 B: 和(m!=0)等价 C: 和(m==1)等价 D: 和(m!=1)等价

    • 2

      ‎若给定条件表达式(m)?(a++):(a--),则其中表达式m()。‎ A: 和(m==0)等价 B: 和(m!=0)等价 C: 和(m==1)等价 D: 和(m!=1)等价

    • 3

      ‏若给定条件表达式(M)?(a++):(a--),则其中表达式M( )。‌ A: 和(M==0)等价 B: 和(M==1)等价 C: 和(M!=0)等价 D: 和(M!=1)等价

    • 4

      若给定条件表达式(M)?(a++):(a--),则其中表达式M( )。 A: 和(M==0)等价 B: 和(M!=1)等价 C: 和(M==1)等价 D: 和(M!=0)等价